1000 botanical colors : make your own dyes, paints, inks, stains, and pottery paints from 250 plants - Warnock, Caleb (Caleb J.), 1973- (Familius, 2025)
No need for store-bought paint when you can learn to make your own natural inks and dyes from plants and flowers Nature provides a rich palette of colors and tones from the plants and flowers around us. Join Caleb Warnock, creator of the Backyard Renaissance series, and create your own natural colors for painting on paper or pottery and dying cloth. With swatches of each shade to find your perfect match, information about each of the over 250 plants, and detailed instructions to make your own paints, inks, and dyes, 1000 Botanical Colors is the home artist's ultimate guidebook.